А )log1\3 (3 - 2x) = -3 б) log12(x + 3) + log12(x + 2) = 1

0 голосов
141 просмотров

А )log1\3 (3 - 2x) = -3 б) log12(x + 3) + log12(x + 2) = 1


Алгебра (12 баллов) | 141 просмотров
Дано ответов: 2
0 голосов

Ответ:

а) x = -12

б) x = 1

Объяснение:

a) log 1/3 (3 - 2x) = -3

-3 = log 1/3 (27)

Итого

log 1/3 (3 - 2x) = log 1/3 (27)

3 - 2x = 27

2x = -24

x = -12

б)  log12(x + 3) + log12(x + 2) = 1

По свойству логарифма:

log12(x + 3) + log12(x + 2) = log12 ((x+3)(x+2))

Распишем единицу:

1 = log12 (12)

Итого

log12 ((x+3)(x+2)) =  log12 (12)

(x+3)(x+2) = 12

x^2 + 5x + 6 = 12

x^2 + 5x - 6 = 0

По теореме Виета

x = -6

x = 1

Проверим :

x = -6 не корень, так как нарушается ОДЗ логарифма (x + 3 ≥ 0 )

Следовательно x = 1

(671 баллов)
0 голосов

А) (3-2х)=1/3 ^ -3. Б) (х+3)*(х+2) =12^1
(3-2х)= 3^3. x^2+5x+6=12
3-2х=27. x^2+5x-6=0
-2х=24. X=1, x=-6
Х=-12

(66 баллов)